Pembuatan Video Tutorial Bedak Dingin Berbahan Dasar Beras dan Ekstrak Singkong - Gabby Rizky Nindy Putri; Mari Okatini Armandari (Jurnal Tata Rias, 2023)
Making a Video Tutorial on Cold Powder Based on Rice and Cassava Extract, Final Project: Diploma 3 Study Program in Makeup, Faculty of Engineering, Jakarta State University, 2022. Cold powder, also known as a traditional mask, is a beauty product that our ancestors have made generation after generation, using white rice mixed with rose water. In the manufacturing process, cold powder is divided into various basic ingredients, including rice and cassava extract. This research was conducted to enhance the knowledge of researchers and readers through a video tutorial on cold powder made from rice and cassava extract. The assessment of this cold powder tutorial video was conducted through a feasibility test by two experts: material experts and media experts. The evaluation considered the following aspects: content, visual, audio, language, and typography. Based on the assessment by material and media experts, "Making a Video Tutorial on Cold Powder Based on Rice and Cassava Extract" was declared feasible.